Relationship between Problematic Internet Uses with Sleep Problem and Psychological Distress among Medical Students (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Problematic Internet use (PIU) is a growing concern, particularly among medical students who face significant academic pressures. This study investigates the relationship between PIU, sleep problems, and psychological distress among medical students of Bangladesh and Nepal.Objectives: To assess the prevalence of PIU and its associations with insomnia, depression, anxiety, and stress among medical students.Methods: A cross-sectional observational design was employed, involving a multiphase sampling technique that excluded students with comorbid psychiatric or medical conditions. Data were collected from 100 fifth-year medical students (23rd batch, 2019-2020 session) through self-administered questionnaires. Instruments included the Internet Addiction Test (IAT), Insomnia Severity Index (ISI), and Depression Anxiety Stress Scale (DASS-21). Statistical analyses were performed using SPSS version 25, applying appropriate tests to determine relationships among variables.Results: The results revealed significant PIU prevalence, with 48% exhibiting mild addiction and 6% severe addiction. A significant relationship between internet addiction and insomnia was identified (p = 0.021), with higher addiction levels correlating with increased insomnia severity. While depression levels showed a trend towards significance (p = 0.067), anxiety and stress did not demonstrate significant associations with PIU (p = 0.622 and p = 0.25, respectively). Gender differences were observed, with females showing higher rates of mild addiction and males’ higher rates of moderate to severe addiction.Conclusion: The study emphasizes the importance of addressing PIU as a public health concern among medical students, integrating mental health support and educational resources to mitigate its adverse effects on well-being and academic performance.J Shaheed Suhrawardy Med Coll 2023; 15(2): 25-33